Anatomy of maize roots in compacted soil - Bergamin, Anderson Cristian; Vitorino, Antonio Carlos Tadeu; Lempp, Beatriz; Souza, Cristiano Márcio Alves de; Souza, Fábio Régis de (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the relationship between maize root anatomy and physical attributes of soil subjected to levels of compaction. The experiment was carried out in field conditions, in Dourados, Mato Grosso do Sul state, Brazil, in a clayed Latossolo Vermelho (Rhodic Acrustox). A randomized complete block design was used, with five replicates. The soil was cultivated for eight years under no-tillage. The additional compaction of the soil was done by tractor traffic in one (PDc1), two (PDc2), four (PDc4) and six successive passes (PDc6), in the entire area of the experimental plots. Ratio between the cortex and vascular cylinder of the root increased with soil compaction. This ratio was negatively correlated to macroporosity, and positively to soil density and soil penetration resistance. Soil compaction level affects the anatomy of maize roots, and its penetration resistance is the best physical indicator to express this effect.
Keywords: Zea mays; root anatomy; physical attributes; soil density; soil porosity; resistance to penetration